A Calm mom–baby happy: utilizing lemongrass peel aromatherapy to treat baby blues syndrome in postpartum mothers - Raffiky Sustamy; Wiwik Muhidayati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: In Indonesia, the prevalence of Baby Blues Syndrome is relatively high. The Ministry of Health (2023) reported an incidence rate ranging from 50%–70%, or approximately 1–2 cases per 1,000 births. Furthermore, data from the National Population and Family Planning Agency shows that approximately 57% of mothers experience symptoms of baby blues, making Indonesia one of the countries with a high prevalence in Asia. If left untreated, this condition can negatively impact the mother-baby relationship and increase the risk of postpartum depression. The